Fluorescent analogs of peptoid-based HDAC inhibitors: Synthesis, biological activity and cellular uptake kinetics. Issue 19 (1st October 2019) - Raudszus, Rick; Nowotny, Robert; Gertzen, Christoph G.W.; Schöler, Andrea; Krizsan, Andor; Gockel, Ines; Kalwa, Hermann; Gohlke, Holger; Thieme, René; Hansen, Finn K.
Graphical abstract: Abstract: Fluorescent tagging of bioactive molecules is a powerful tool to study cellular uptake kinetics and is considered as an attractive alternative to radioligands. In this study, we developed fluorescent histone deacetylase (HDAC) inhibitors and investigated their biological activity and cellular uptake kinetics. Our approach was to introduce a dansyl group as a fluorophore in the solvent-exposed cap region of the HDAC inhibitor pharmacophore model. Three novel fluorescent HDAC inhibitors were synthesized utilizing efficient submonomer protocols followed by the introduction of a hydroxamic acid or 2-aminoanilide moiety as zinc-binding group. All compounds were tested for their inhibition of selected HDAC isoforms, and docking studies were subsequently performed to rationalize the observed selectivity profiles. All HDAC inhibitors were further screened in proliferation assays in the esophageal adenocarcinoma cell lines OE33 and OE19. Compound 2, 6-(( N -(2-(benzylamino)-2-oxoethyl)-5-(dimethylamino)naphthalene)-1-sulfonamido)- N -hydroxyhexanamide, displayed the highest HDAC inhibitory capacity as well as the strongest anti-proliferative activity. Fluorescence microscopy studies revealed that compound 2 showed the fastest uptake kinetic and reached the highest absolute fluorescence intensity of all compounds. Hence, the rapid and increased cellular uptake of 2 might contribute to its potent anti-proliferative properties.